2013
DOI: 10.1007/s11266-013-9372-7
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory Public Benefit Reporting as a Basis for Charity Accountability: Findings from England and Wales

Abstract: Charitable status is inherently linked in many jurisdictions with the requirement that an entity must be established for public benefit. But, until recently the public benefit principle had relatively little impact on the operations of most established charities. However, in England and Wales, reforms linked to the Charities Act 2006 led to a new requirement for public benefit reporting in the trustees' annual report (TAR) of every registered charity. This new narrative reporting requirement had the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 30 publications
(21 reference statements)
6
45
0
Order By: Relevance
“…Table , panel C shows that three quarters of the NPOs represented by our survey respondents had income of less than £3m. This is consistent with the profile of the NPO/charity sector generally, which is populated mainly by small organisations (Cordery, ; Morgan & Fletcher, ). It may be that, in our sample, the perceptions of those involved in financial reporting of smaller NPOs are significantly different from those involved with big NPOs, and further statistical analysis would be required to test this.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Table , panel C shows that three quarters of the NPOs represented by our survey respondents had income of less than £3m. This is consistent with the profile of the NPO/charity sector generally, which is populated mainly by small organisations (Cordery, ; Morgan & Fletcher, ). It may be that, in our sample, the perceptions of those involved in financial reporting of smaller NPOs are significantly different from those involved with big NPOs, and further statistical analysis would be required to test this.…”
supporting
confidence: 86%
“…For any such development, it may be tempting to prioritise the views of trustees/board members over other stakeholders, given their instrumentality in driving NPO reporting quality (Coule, ; Morgan & Fletcher, ). However, the trustee group in our research showed significant differences in their thinking compared with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The schools, which are listed anonymously in Table 1 with their characteristics, were recruited through personal and professional contacts and via a private school membership organisation. We also consulted the school trustees' annual reports to the Charity Commission: as with all charities, these contain some limited narrative reporting on public benefit activities (Morgan and Fletcher, 2013). To obtain the perspectives of other key stakeholders, we interviewed headteachers of four state schools (also listed in the table) and, for an informed sector perspective, the directors of two private school associations.…”
Section: Methodsmentioning
confidence: 99%
“…Reporting takes many forms presently. New mandatory mechanisms to enhance accountability appear in other countries, for example, public benefit reporting in the trustees' annual report in England and Wales (Morgan & Fletcher, 2013).…”
Section: Complexity and Diversity Of Accountabilitymentioning
confidence: 99%